Technique for the imaging crystalline basement according to the DSS data - О. О. Верпаховська (Геофизический журнал, 2021)
The method of deep seismic sounding (DSS), the observation systems in which are characterized by an irregular arrangement of both sources and receivers along the profile, a significant step between receivers, as well as maximum source-receiver distances exceeding several hundred kilometers, makes it possible to obtain an image of the crystalline basement using seismic migration fields of reflected/refracted waves. The main part of the existing migration methods, the use of which makes it possible to form an image of the deep structure of the study area in the dynamic characteristics of the recorded wave field, is focused on processing seismic data obtained by the method of reflected waves with multiple overlap observation systems (MOV—CDP). And, as a rule, these migration methods are designed for a smooth change in speed with depth. At the same time, at the boundary of the crystalline basement, the speed changes very sharply, which must be taken into account when processing data using migration.